Generating power from fluegas produced by boilers through thermodynamic organic rankine cycle - Rowshanaie, Omid (2015)
A simulation model of Organic Rankine Cycle (ORC) was developed with HYSYS simulation software driven by R245fa, with NOVEC7000 and R141b as refrigerant working fluids and wet fluegas combustion and burning from natural gas, as a heat source of shell and tube heat exchanger to generate optimum power by an expander (more than 3MW that proper amount of energy for applying in refinery and petrochemical industries). The initial operating conditions were in subcooled liquid,normal, and steady state condition. In current ORC, refrigerant working fluids were sent to a heat exchanger to change the phase fraction from 0 to 1, then input to an expander to produce optimum power. However, the changing of all parameters were affected by different mass flow rates of working fluids and different inlet pressures of expander. The ORC thermodynamic cycle was chosen for this study due to some advantages such as its simple structure, the availability of its components, and the ease of application for small and optimum industrial power generation. Regarding to current study results, different mass flow rates of working fluids and different inlet pressures of expander had linear relationship with power output from the expander. Therefore, R141b was found to be produced the highest power output from the expander up to 13520 KW, compared to NOVEC7000 where by the power being produced 35 % less and the lowest power generated by the expander belonged to R245fa refrigerant with 53 % reduction. Also the highest net power generated output from the ORC was from R141b which the highest power was 12194 KW,followed by NOVEC7000 and R245fa gave as the lowest net power output, 37 % and 57 % reduction respectively. For the heat transfer from the fluegas to the working fluid ascendancy; R141b with 3.780×109 kJ/h, then R245fa 18 % less and NOVEC7000 38 % reduction respectively. Furthermore, in terms of total efficiency of ORC depend on different inlet pressures of expander, NOVEC7000 was chosen as highest total efficiency with 90.8 % and R141b was chosen as middle total efficiency with 90.6 % were the suitable options compare with R245fa which value was i.e. 85.0 % the lowest total efficiency of ORC. The thermal efficiency of the ORC for different mass flow rates of working fluids and different inlet pressures of expander were analyzed and there were no remarkable differences between R245fa, NOVEC7000, and R141b. The polytropic efficiency of the expander was evaluated at different specific pressures of each working fluid at the inlet of expander. The result was indicated NOVEC7000 superior in which it given 80.3 % of the polytropic efficiency followed by R141b and R245fa with 70.5 % and 40.1 % respectively. On the other hand, no remarkable difference of the exergy efficiency for the ORC at maximum total irreversibility and maximum heat exchanger exergy of present ORC.